Strategi Komunikasi Internal dalam Transformasi Identitas Organisasi: Studi Kasus PT Pantau Sumber Berita dari Media Online Menuju Content Creator Berbasis Media Sosial - Aditya Andreas; Agung Sukariman Putra (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
Digital transformation has compelled media companies to reshape their business models, work culture, and organizational identity to remain relevant within algorithm-driven social media ecosystems. This study aims to analyse the internal communication strategies of PT Pantau Sumber Berita in managing its identity transformation from an online news portal into a digital platform-based content creator organization. The research employed a qualitative single case study approach, utilizing in-depth interviews, observation, and internal document analysis. The findings reveal that successful transformation was determined by the effectiveness of internal communication across three stages of organizational change: unfreezing, through building urgency and deconstructing the previous journalistic identity; moving, through sense-giving, dialogic communication, and work culture adaptation; and refreezing, through the institutionalization of a new identity based on KPI systems,,. Furthermore, the study identifies resistance rooted in identity ambiguity, increased workload, and the inherent tension between journalistic depth and algorithmic demands for brevity and engagement,,. The implications suggest that internal communication serves as a core strategic mechanism in media transformation by functioning as an arena for identity negotiation and sustainable cultural reconstruction.